New maps representing the historical and recent distribution of the African species of rhinoceros: Diceros bicornis, Ceratotherium simum and Ceratotherium cottoni - Rookmaaker, Kees; Antoine, Pierre-Olivier (Pachyderm, 2012)
The paper presents new and updated maps showing the historical and current range of the black, white and Nile rhinoceros. Distribution of the species is based on written and iconographical records, as well as museum specimens. The historical range reflects the situation from ad 1500 onwards (or the last part of the Holocene). The current range is divided into original and introduced populations. Cet article présente de nouvelles cartes mises à jour qui montrent l’habitat historique et actuel du rhinocéros noir, blanc et du Nil. La distribution de l’espèce est basée sur des rapports écrits et iconographiques ainsi que sur des spécimens dans les musées. L’habitat historique reflète la situation à partir de l’année 1500 et après (c’est-à dire la dernière partie de l’Holocène). L’habitat actuel est divisé d’après des populations originelles et introduites.